Implementation of Digital Marketing Strategy with SOSTAC Model Approach in Increasing the Attractiveness of Prospective New Students - Imroah Muflihah; Hadiah Fitriyah (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to implement a digital marketing strategy using the SOSTAC model approach in increasing the attractiveness of prospective new students. An excellent framework for digital marketing strategy planning is the SOSTAC Model, which stands for Situational Analysis, Objectives, Strategies, Tactics, Actions, and Control. The SOSTAC model can pinpoint the most important aspects of marketing analysis and planning that must be considered to achieve goals. Educational institutions are required to provide accurate and transparent information to prospective students and parents. This research uses a qualitative approach. The type of data in this study is a type of qualitative data in the form of interview results, and the type of data is primary data collected through interviews and observations. The analysis technique used triangulation technique. The results of this study show that the school has identified strengths, opportunities, weaknesses and threats faced in the school environment that continue to grow. This provides strong basis in the implementation of a good digital marketing strategy by adopting the analysis of the strategy set. The application of the 4P marketing mix (Place, Promotion, Price and People) helps to design an effective digital marketing strategy. Schools can also design, control and evaluate the implementation of digital marketing strategies through websites and social media (ig, and FB) effectively.